Reclaiming the womb: Towards an Irigarayan direction of the monstrous womb in pregnancy horror films - Aldecoa, Cristina Louise B (Animo Repository, 2025)
Horror films have served as space to propagate the victimization, objectification, and sometimes villainization of women. Among many of the female archetypes in horror, the so-called monstrous womb of the monstrous feminine archetype coined by Barbara Creed highlights this feature most. It is argued that the maternal body is considered as an “abjection” ⎯ that which disturbs identity, order, and boundaries ⎯ thus, the feminine/womb labeled as monstrous. The grotesque reimagining of pregnancy and childbirth in horror films underscores the sexual difference between men and women, insofar that women are portrayed to experience drastic changes in their bodies during pregnancy and an abnormal life form growing inside/coming outside of them through childbirth. This highlights the problem of sexual difference that Irigaray talks about. In her theory, she argues that the construction of the concept of “human” has been framed by the language, culture, and laws from the male perspective, thus disregarding the female perspective and experience. Moreover, pregnant women in horror films have persisted to be portrayed as as monstrous because of deeply entrenched ideas set by the symbolic order. Following her theory, structural change must be made in the way women are viewed as subject/object especially in mediums such as horror films that propagate this. In this paper, I shall reveal that it is possible to deviate from the phallocentric notion of the monstrous womb exhibited in horror films by centering a film’s narrative on the female experience of pregnancy and subjectivity. The goal of this paper is twofold: 1.) To shift the discourse of the monstrous womb to a female perspective; and 2.) To use this perspective of the monstrous womb in the context of sexual difference. As such, I claim that there is no such thing as a monstrous womb and that its depiction in horror films must be well represented by a woman’s lived experience of pregnancy, subjectivity, and embodiment. Furthermore, the theory of sexual difference shall be used as a framework to strategically mimic and subvert the depiction of the womb in an ontological and existential dimension through an analysis of the film, Huesera: The Bone Woman.